Effects of Division I tennis athletes grip strength on serve velocity - Bonnette, R. (The Journal of Strength and Conditioning Research, 2021)
Purpose: The purpose of this study was to investigate the effect of grip strength on tennis serve velocity of NCAA Division I Male and Female Tennis athletes. Methods: Fifteen NCAA Division I college tennis athletes (7 females, 8 males) participated in this study. During the fall offseason, subjects were tested to obtain the grip strength of their dominant serving hand and determine their maximum serve velocity. Prior to serving the athletes grip strength was assessed using a Hydraulic Hand Dynamometer. Once completed, subjects were put through a brief warm-up consisting of dyna-band exercises for the shoulder complex and practice serves. Once sufficiently warm, each athlete completed 10 serves. Their maximum velocity was recorded using a Stalker Sport 2 radar gun. Results: There was a significant positive correlation between grip strength and serve velocity (r = 0.554, p = 0.032). Conclusions: The current findings demonstrated that increased grip strength is related to greater serve velocity. These results suggest that NCAA tennis players may improve service performance in relation to increased velocity by increasing their grip strength. Practical Applications: Collegiate strength coaches that work with tennis athletes should create specific training regimens and exercises to improve their athlete's grip strength.